ABOUT HUMANISTIC NATURE OF CULTURAL HERITAGE AND CHALLENGES OF CONTEMPORARY TIME - Vladimir I. Ionesov (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
This article tries to show humanistic nature of heritage, its place and role in changing world in context of challenges of contemporary time. Author does attempt to show how the heritage to influence on cultural process and social changes in turbulent time, but also why world heritage is imperative of survival, intercultural reconciliation and sustainable development of humanity. It is emphasized the role and place of heritage in cultural system and social practice. Acknowledging that the diverse interpretations of concept ‘heritage’ are insufficient and too common, the author presents his interrogation of phenomenon of cultural heritage in discourse of cultural-anthropological knowledge. The article seeks to foreground the ontological parameters of world heritage, which it is considered in context of philosophy of “trace”, “sign” and “memory”. The main hypothesis of the author is that heritage and its artefacts express the materialized (or verbalized) manifestations of memory or memorial culture that is general human constants and social values, which create and support the protective environment for survival of culture and overcoming of global challenges. The main of argument author is that heritage presents the cultural patterns and area of constancy in changing society and thanks to it the culture can support its functional viability in turbulent time. The heritage enables to create the new structuring of cultural system, including integration of past and present, local and universal, artificial and natural, mental and material.